PENGARUH CAIRAN TUBUH MANUSIA TERHADAP KOROSI PADA PLAT PENYAMBUNG TULANG - Nani Mulyaningsih (Wahana Ilmuwan, 2017)
Bone connective plate material usually made of SS316L, which has corrosion resistant properties but are expensive so that it becomes an obstacle to the people's purchasing power. Selection of SS 304 at this research that as an alternative to 316L SS, which aims to compensate 316L SS in terms of corrosion rate. So, we need a process to reduce the rate of corrosion SS 304, one way is by electroplating Ni-Cr. This study aims to determine the effect of variations in time (8, 17, 25, 30, 40 minutes) used in Ni-Cr electroplating processes in materials SS 304, the corrosion rate. This research method is performed by electroplating material SS 304 with Ni-Cr and then the material is tested corrosion. Testing corrosion rate using three-electrode cell with media PBS (Phosphate Baver Salin). The optimum time and the lowest corrosion rate of Ni-Cr electroplating process on the SS 304 is achieved by electroplating 17 minutes long. The result showed that the electroplating process can reduce the rate of corrosion on the surface of SS 304 Lapis Ni-Cr. 304 SS corrosion rate of 0.0009423 mm/yr, after dielectroplating Ni-Cr decreased by 60.9% to 0.000368 mm/yr.